IT workers shortage: implications for educational policy. - Wilson, Vlay (Policy Studies Review)
This article examines the information technology (IT) worker shortage by comparing the rate of salary increase for IT workers from 1995 to 1998 to the rate of inflation for those same years. Findings show that the median salary for IT workers has increased at twice the rate of inflation. Universities and businesses form partnerships to develop innovative products. Continuous innovation has meant that both industry and universities require workers, students and faculty to continuously change their skill sets. At every point as technology changes there is a shortage of the newest combination of required skill sets. A recommendation is made to change education strategy so IT workers have easier access to continuous education via the Internet, funded by their employers. Reprinted by permission of the publisher.